Taxpayer Compliance: Average Effective Rate Of Income Tax Article 21 And Taxation Socialization - Amin, Nurul Fitria Rahmadany; Parwati, Ni Made Suwitri (Accounting Studies and Tax Journal (COUNT), 2024)
Tax compliance is considered a crucial element affecting state revenue, mainly through Income Tax Article 21. This topic was chosen because the latest policy regarding Income Tax Article 21 rates calculation is expected to impact taxpayer compliance. The investigation examines how taxpayers feel about applying Income Tax Article 21's average effective rate and how tax socialization affects taxpayer compliance with filing the Annual Tax Return (SPT). The analysis population includes 6,782 ASN taxpayers in Palu City. The quantitative research process involves giving respondents questionnaires.Three hundred seventy-eight respondents The accidental sampling approach was used to pick respondents randomly, and the number of respondents in this To test the hypothesis research. The idea was tested using Warp PLS 7.0 sof. The findings demonstrated how tax socialization and applying Article 21's Average Effective Rate of Income Tax impacted taxpayer compliance with filing tax returns.. This research is expected to contribute to tax authority policy. With this insight, tax authorities will be better able to design more appropriate policies that encourage taxpayer compliance in reporting their obligations.